2020
DOI: 10.3390/app10176026
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative Mist Cooling as Heat Dissipation Technique: Experimental Assessment and Modelling

Abstract: The severity of extreme weather conditions brought on by climate change are conditioning quality of life, economic development, and well-being in today’s cities. Conventional measures have been shown to be insufficient for tackling climate change and must be supplemented with ecofriendly approaches. Hence, the scientific community’s endeavor to develop natural cooling techniques that lower energy consumption while delivering satisfactory comfort levels. For its simplicity and low cost, evaporative cooling has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The air temperature in open spaces is reduced through natural conditioning techniques that sustainably achieve thermal comfort goals. Nature-based techniques involve the use of environmental heat sinks [35] such as the air, the ground and the sky, and the primary technology highlighted in the literature consists of the use of underground pipes [36], evaporative cooling [37] and/or radiative cooling [38].…”
Section: Climate Control Of Outdoor Spacesmentioning
confidence: 99%
“…The air temperature in open spaces is reduced through natural conditioning techniques that sustainably achieve thermal comfort goals. Nature-based techniques involve the use of environmental heat sinks [35] such as the air, the ground and the sky, and the primary technology highlighted in the literature consists of the use of underground pipes [36], evaporative cooling [37] and/or radiative cooling [38].…”
Section: Climate Control Of Outdoor Spacesmentioning
confidence: 99%
“…Finally, and in general, the temperature reduction was achieved by driving cold air into the space to be conditioned, where the air was cooled through environmental heat sinks [23] and therefore had a higher temperature than cold air used in conventional building conditioning. The use of a natural sink for air cooling is possible with known techniques such as evaporative cooling [24] and innovative systems such as the "falling-film system" [25].…”
Section: Bioclimatic Techniquesmentioning
confidence: 99%
“…Recent studies have shown that if temperatures arose as predicted, worldwide residential energy consumption for cooling will be up to 34% higher than at present in 2050 and 2100 up to 61% greater [19]. Now we need to make our systems as efficient as possible to meet the growing energy demands without creating any extra carbon foot print and climate change [7]. Various techniques to increase the COP of refrigeration cycle are air cooled; water cooled evaporatively cooled condensers and compressor shell and use of high conductivity nano materials to increase the heat transfer coefficient [1].…”
Section: Introductionmentioning
confidence: 99%
“…Burning fossil fuels creates the global warming, climate change and deforestation [10]. This in turn creates the demand of cooling and refrigeration systems [7]. Throughout the development path of sciences various methods of cooling, refrigeration and air conditioning viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation